Mindfulness and Lavender Aromatherapy Techniques for Anxiety in Cervical Cancer Patients Those Undergoing Chemotherapy: Literature Review - Rosniati Rosniati; Erika Erika; Nurul Huda (GLOBAL HEALTH SCIENCE GROUP, 2024)
One disease that is considered very scary in society is cancer. Treatment such as chemotherapy is needed to kill cancer cells. However, chemotherapy also has side effects both physical and psychological. Psychological disorders occur such as feeling anxious or worrying too much about something that can affect the ability to carry out activities. One of the psychological therapies carried out is mindfulness techniques and lavender aromatherapy to reduce anxiety levels in cervical cancer patients undergoing chemotherapy. Mindfulness techniques can provide benefits for cancer patients in achieving relaxation of anxiety during chemotherapy treatment. Apart from mindfulness techniques, providing aromatherapy is also an alternative for reducing anxiety in patients undergoing chemotherapy. The aromatherapy used to reduce anxiety is the aroma of lavender. Lavender aromatherapy can reduce anxiety and stress because it has relaxing properties that can have a positive effect on the nervous system and mood. The scent of lavender can stimulate receptors in the nose that are connected to the brain and stimulate the release of chemicals such as serotonin which can improve mood. The design used is a literature review, articles were collected using academic databases used in this search, namely Pubmed, Google Scholar, Science Direct with research articles published from 2019 - 2023. Based on the articles collected, we obtained review results from 21 journals that show mindfulness. and aromatherapy can help a person manage anxiety, including anxiety that may arise in connection with cervical cancer and the chemotherapy process.